Sistem Informasi Pemeriksaan Tes Covid-19 Untuk Fasilitas Pelayanan Kesehatan (Fasyankes) - Andy M. Sudartono; Rohmat Nur Ibrahim; Ali Mulyawan (Jurnal Computech & Bisnis (e-journal), 2022)
To strengthen the government's program in the form of 3T (Testing, Tracing, Treatment) in controlling the Covid-19 pandemic in Indonesia, required an integrated screening test web-based information system (software) for patients, referrals, laboratories designed to follow the needs and flows in the field to issue test results quickly and accurately. The research method used is qualitative-descriptive, with a System Development Life Cycle (SDLC) method. This software is designed using the Laravel Framework 8.0 and using MySQL database for data storage, also using UML (Unifield Modeling Language) as a tool for system design. System testing techniques using the black box method. The problems of speed of time, automation, and data accuracy that arise in the health facility referral will be resolved by providing a fast, accurate and integrated solution for test results.